Analysis of The E-Readiness of The Development Evaluation and Control System (ASEUPAN) Application in Pandeglang Regency - Raden Aria Cakraningrat; Anis Fuad (Anthroposia: Journal of Social and Human Development, 2026)
This study examines the electronic readiness of users of the Development Evaluation and Control System Application known as ASEUPAN in Pandeglang Regency. The research employed a quantitative empirical approach using the STOPE plus Budget framework to evaluate readiness across the dimensions of Strategy, Technology, Organization, People, Environment, and Budget. Data were collected through a census survey involving fifty civil servants, administrators, and system operators who actively utilized ASEUPAN. The instrument consisted of twenty five measurement items assessed using a four point Likert scale and analyzed through descriptive statistics using IBM SPSS Statistics 26. The findings indicate that users exhibit a favorable level of readiness across all assessed dimensions. Strategic alignment and technological capability support the operational utilization of the application, while organizational commitment and human resource competence strengthen implementation effectiveness. Regulatory support, interagency collaboration, and sustainable financial resources contribute to the continuity of digital governance initiatives. The study highlights that successful digital government implementation depends on the integration of technological, organizational, human, environmental, and financial factors. These findings provide practical insights for strengthening digital governance capacity and supporting sustainable public sector transformation in local government institutions.